Pangenomics of flax fungal parasite Fusarium oxysporum f. sp. lini - Logachev, Anton; Kanapin, Alexander; Rozhmina, Tatyana; Stanin, Vladislav; Bankin, Mikhail; Samsonova, Anastasia; Orlova, Ekaterina; Samsonova, Maria (Frontiers in Plant Science, 2024)
To assess the genomic diversity of Fusarium oxysporum f. sp. lini strains and compile a comprehensive gene repertoire, we constructed a pangenome using 13 isolates from four different clonal lineages, each exhibiting distinct levels of virulence. Syntenic analyses of two selected genomes revealed significant chromosomal rearrangements unique to each genome. A comprehensive examination of both core and accessory pangenome content and diversity points at an open genome state. Additionally, Gene Ontology (GO) enrichment analysis indicated that non-core pangenome genes are associated with pathogen recognition and immune signaling. Furthermore, the Folini pansecterome, encompassing secreted proteins critical for fungal pathogenicity, primarily consists of three functional classes: effector proteins, CAZYmes, and proteases. These three classes account for approximately 3.5% of the pangenome. Each functional class within the pansecterome was meticulously annotated and characterized with respect to pangenome category distribution, PFAM domain frequency, and strain virulence assessment. This analysis revealed that highly virulent isolates have specific types of PFAM domains that are exclusive to them. Upon examining the repertoire of SIX genes known for virulence in other formae speciales, it was found that all isolates had a similar gene content except for two, which lacked SIX genes entirely.